2001
DOI: 10.1248/bpb.24.470
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Immunomodulating Properties of a Sterol Fraction from Sideritis foetens Clem.

Abstract: Interest in the phytochemical study of species of the Sideritis genus (Lamiaceae) has been stimulated by their pharmacological activity and their wide range of medicinal folk uses in Spain such as vulnerary, anti-infectious, anti-inflammatory, anti-rheumatic and anti-ulcerous applications. Various flavonoids and terpenoids have been isolated from this genus. 1,2) We have recently reported the anti-inflammatory properties of a lipid fraction obtained from Sideritis javalambrensis and those of the diterpenoid (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 25 publications
6
67
1
1
Order By: Relevance
“…Studies have shown that sterolenriched (such stigmasterol and sitosterol) diets reduce the plasma cholesterol concentrations [64,65], have antiinflammatory actions [66,67], and display analgesic and anti-mutagenic effects [67,68]. Moreover, Yun et al [69] used a mixture of Rg3 and Rg5, present in large amounts in red ginseng, and showed that they reduced the incidence of lung adenoma induced by benzo(a) pyrene in mice to 45.0% (inhibition rate, 25.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sterolenriched (such stigmasterol and sitosterol) diets reduce the plasma cholesterol concentrations [64,65], have antiinflammatory actions [66,67], and display analgesic and anti-mutagenic effects [67,68]. Moreover, Yun et al [69] used a mixture of Rg3 and Rg5, present in large amounts in red ginseng, and showed that they reduced the incidence of lung adenoma induced by benzo(a) pyrene in mice to 45.0% (inhibition rate, 25.0%).…”
Section: Discussionmentioning
confidence: 99%
“…In ovalbumin-induced asthmatic mice, lung inflammation related to leukocytosis and eosinophil infiltration was reduced by intraperitoneal injection of beta-sitosterol [61]. Oral consumption or topic application of a single dose of a phytosterol mixture containing mainly beta-sitosterol was also shown to decrease or even inhibit oedema in murine models of inflammation [62]. However, results from other studies in animal models do not support a role for beta-sitosterol in preventing or reducing inflammation [63,64].…”
Section: Anti-inflammatory Effects and Effects On The Immune Systemmentioning
confidence: 99%
“…Some plant extracts that have proven eOE ective in in¯ammation or anti-NF-j B activity include the commonly used phytomedicine stinging nettle (Urtica dioica, Urticaceae ; Riehemann et al 1999), Siderites foetens Clemen. (Lamiaceae) (Navarro et al 2001), a commercially obtained extract of Ginkgo biloba (Ginkgoaceae) (Wei et al 1999), Siderites javalambrensis (Godoy et al 2000), Uncaria tomentosa (Cat's claw, Rubiaceae ; SandovalChaco! n et al 1998), Drosera madagascariensis (Droseraceae ; Melzig et al 2001), Tripterygium wilfordii Hook F. (Sylvester et al 2001) and a bio¯avonoid extract from Pinus maritima (Pinaceae) (Cho et al 2000).…”
Section: Other Compounds and Plant Extractsmentioning
confidence: 99%